Global Perspective on the Natural History of Chronic Hepatitis B: Role of Hepatitis B Virus Genotypes A to J - Liu, Chun-Jen; Kao, Jia-Horng (Seminars in Liver Disease, 2013)
Clinical outcomes of chronic hepatitis B virus (HBV) infection vary widely. In addition to host factors, several viral factors including HBV genotype, viral load, specific viral mutations and quantitative HBsAg levels, have been associated with disease outcomes. Among viral factors, HBV genotype correlates with not only the clinical outcomes, but also with the response to interferon treatment. Currently, 10 HBV genotypes have been identified. Compared with genotype A and B cases, patients with genotypes C and D have lower rates and usually delayed onset of spontaneous HBeAg seroconversion. HBV-genotype C has a higher frequency of basal core promoter (BCP) A1762T/G1764A mutation and preS deletion, and a higher viral load than genotype B. Similarly, genotype D has a higher prevalence of BCP A1762T/G1764A mutation than genotype A. These observations suggest pathogenic differences between HBV genotypes. Genotyping of HBV can help practicing physicians identify chronic hepatitis B patients at risk of disease progression.
Keywords: hepatitis B virus; genotype; viral load; HBsAg level; hepatocellular carcinoma; cirrhosis